Concept of Corruption, Essence and History of Emergence - Bekdavlat Aliev (Periodica Journal, 2023)
Corruption is a social evil that has a huge negative impact on the development of society. Nowadays, there is a fight against this disease on a global scale. The article discusses the concept of corruption, its essence and history of its emergence. The author provides comprehensive information about corruption based on various scientific sources. In recent years, anti-corruption policies, presidential decrees, Cabinet of Ministers decisions and other various legal documents increase the relevance of the topic. During the research, an attempt was made to provide a solution to the problem posed by the topic using methods of scientific knowledge such as historical, comparative analysis, logic, analysis and synthesis
Keywords: Corruptio; Corruption; bribery; lobbying